Chronic myelomonocytic leukemia: Forefront of the field in 2015. Issue 2 (August 2015) - Benton, Christopher B.; Nazha, Aziz; Pemmaraju, Naveen; Garcia-Manero, Guillermo
Abstract Chronic myelomonocytic leukemia (CMML) includes components of both myelodysplastic syndrome and myeloproliferative neoplasms and is associated with a characteristic peripheral monocytosis. CMML is caused by the proliferation of an abnormal hematopoietic stem cell clone and may be influenced by microenvironmental changes. The disease is rare and has undergone revisions in its classification. We review the recent classification strategies as well as diagnostic criteria, focusing on CMML's genetic alterations and unique pathophysiology. We also discuss the latest molecular characterization of the disease, including how molecular factors affect current prognostic models. Finally, we focus on available treatment strategies, with a special emphasis on experimental and forthcoming therapies.